Pre-Service Teachers Perceptions and Knowledge in Padangsidimpuan City : Concepts of Trigonometric - Siregar, Torang (Al-Khawarizmi, 2023)
AbstractThis paper explored pre-service teachers’ perceptions and knowledge of trigonometric concepts. Convenience sampling technique was used to select a sample of 200 (50 females, 150 males) second year science/mathematics pre-service teachers from two Colleges of Education in the Padangsidimpuan City. Trigonometry Perception Questionnaire (TPQ) and Trigonometry Assessment Test (TAT) were used to collect data on pre-service teachers’ perceptions and conceptual knowledge of trigonometry. Data were coded and keyed into Statistical Package for Service Solutions (SPSS version 20) and analysed using descriptive statistics. The results suggested that pre-service teachers perceived trigonometry as abstract, difficult and boring to learn; and had limited conceptual knowledge of basic trigonometric concepts. Consequently, more that 65 % of them were unable to construct and reconstruct the appropriate mental structures for meaningful understanding to enable them respond to important basic trigonometry tasks. To achieve quality mathematics education, teacher educators must change their instructional practice and teach for understanding. Since understanding is the key to teacher’s instructional actions, processes and knowledge, we recommend teaching trigonometry for understanding during teacher preparation.